2022
DOI: 10.1128/cmr.00008-21
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Human Infection Models To Accelerate Vaccine Development

Abstract: The timelines for developing vaccines against infectious diseases are lengthy, and often vaccines that reach the stage of large phase 3 field trials fail to provide the desired level of protective efficacy. The application of controlled human challenge models of infection and disease at the appropriate stages of development could accelerate development of candidate vaccines and, in fact, has done so successfully in some limited cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 819 publications
(989 reference statements)
0
8
0
Order By: Relevance
“…The prevalence of immunizations against infectious illnesses is on the rise and is very effective. In order to ensure the effectiveness of vaccines, the preclinical and clinical stages of vaccine development need the use of intricate, time-consuming, and costly in vivo and in vitro methodologies [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of immunizations against infectious illnesses is on the rise and is very effective. In order to ensure the effectiveness of vaccines, the preclinical and clinical stages of vaccine development need the use of intricate, time-consuming, and costly in vivo and in vitro methodologies [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Controlled human infection models (CHIMs) have a strong track record in accelerating vaccine development, particularly for enteric pathogens. 12 13 For example, the live attenuated cholera vaccine CVD 103-HgR was licensed as a travel vaccine on the basis of safety, immunogenicity and efficacy data arising from CHIM studies. 14 More recently, a programme of typhoidal Salmonella CHIM studies demonstrated efficacy of a Vi-tetanus toxoid (Vi-TT) conjugate vaccine against S .…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution immune profiling of the host peripheral immunity after pathogen exposure, particularly during the pre-symptomatic phase, has largely been limited to human challenge studies (7)(8)(9). Controlled human infection models pose several limitations to understanding the host response during natural infections (10).…”
Section: Introductionmentioning
confidence: 99%
“…High-frequency longitudinal profiling of host peripheral immunity, particularly during extremely early presymptomatic phases, has largely been conducted in the setting of human challenge studies 7-9 . Controlled human infection models pose limitations to understanding the host response during natural infections 10,11 . Restricted by ethical and regulatory considerations, these models often employ use of a limited set of challenge strains, a uniform viral challenge dose, and are performed on low-risk, healthy volunteers (young adults), thus limiting their broad applicability to contemporaneously circulating variants and to the heterogeneity of population-wide immunologic backgrounds that are shaped by individual susceptibilities, and by prior vaccination and infection 11 .…”
Section: Introductionmentioning
confidence: 99%